An investigation into stylistic devices used in “the life we were given” by dana sachs and their vietnamese translational equivalents (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis deals with simile, metaphor and metonymy in “The Life We Were Given” and the translation problems of these stylistic devices. The data is 360 samples (228 simile, 92 metaphor and 42 metonymies) collected in “The Life We Were Given” and its Vietnamese translation version – “Những Mảnh Đời Được Ban Tặng”. The quantitative method, descriptive and analytical method, qualitative method, and contrastive method are exploited in order to help the researcher achieve the aims and objectives proposed. After studying the findings of the thesis, we also recognize that the translator has applied many different translation procedures which are suggested by Peter Newmark to render simile, metaphor and metonymy from English into Vietnamese. Among which, literal translation is the most used procedures for translating simile, metaphor and metonymy as well. Besides literal translation, some procedures such as reduction and expansion are quite commonly-used in translation. Finally, basing on the findings and results of this study, some implications for translation are proposed. During the translation process, the translator must grasp theory of translation and stylistic devices. Furthermore, for the common images in both source language and target language, literal translation seems to be the most effective procedure to render.